Sistema de gestión para la etapa de mantenimiento del área de alcantarillado sanitario en la ciudadela Alborada - Velasco Borja, Guido Enrique (2022)
The present research work entitled "Management system of the maintenance stage of the sewerage area of the Alborada citadel, being the maintenance of sanitary sewers a vital service to meet the needs of users and improve good living, allowing to denote that it exists a deficiency in the maintenance since these are carried out in a corrective maintenance and that during the time they have been generating deficiencies either in the drinking water, sewerage and storm drainage services, therefore this generates a deficiency for the population, environment and the conservation of the Ecological system. The method used in this research work is inductive and deductive; Since Inductive proposes a management system using the necessary tools for the process of the maintenance stage of the sewerage area, and deductive because a statistical descriptive analysis is carried out with the documentary collection of historical data, of maintenance executed during the process. sewer system in the dawn citadel..........